Prospects of China's High-speed Railroad considering the Debate on "Maglev" and "On-the-Trail" Contributions - Run Sha; Shao-Ying Chu (Promet (Zagreb), 2012)
Considering the fierce debate on whether "maglev" or"on-the-trail" system should be applied to China's first high-speed railroad, this paper makes prospects about China's high--speed railroads. As at the initial stage, careful considerationsshould be given to the framework of China's high-speed railroads.Combining China's specific national conditions, the paperdemonstrates that maglev train can be well applied in theeast and the regions of the middle and lower reaches of theYangtze River where there is developed economy, lwge anddense population, limited land use, concentrated big cities andrail transport shortage. The maglev system is the world's mostadvanced technology, China should take the best to catch upwith the world in this transportation field.